Stereo electronic principles for selecting fully-protective, chemically-synthesised malaria vaccines - Patarroyo, Manuel E.; Bermudez, Adriana; Alba, Martha P.; Patarroyo, Manuel A.; Suarez, Carlos; Aza-Conde, Jorge; Moreno-Vranich, Armando; Vanegas, Magnolia (Frontiers in Immunology, 2022)
Major histocompatibility class II molecule-peptide-T-cell receptor (MHCII-p-TCR) complex-mediated antigen presentation for a minimal subunit-based, multi-epitope, multistage, chemically-synthesised antimalarial vaccine is essential for inducing an appropriate immune response. Deep understanding of this MHCII-p-TCR complex’s stereo-electronic characteristics is fundamental for vaccine development. This review encapsulates the main principles for achieving such epitopes’ perfect fit into MHC-II human (HLA-DRβ1* or Aotus (Aona DR) molecules. The enormous relevance of several amino acids’ physico-chemical characteristics is analysed in-depth, as is data regarding a 26.5 ±2.5Å distance between the farthest atoms fitting into HLA-DRβ1* structures’ Pockets 1 to 9, the role of polyproline II-like (PPIIL) structures having their O and N backbone atoms orientated for establishing H-bonds with specific HLA-DRβ1*-peptide binding region (PBR) residues. The importance of residues having specific charge and orientation towards the TCR for inducing appropriate immune activation, amino acids’ role and that of structures interfering with PPIIL formation and other principles are demonstrated which have to be taken into account when designing immune, protection-inducing peptide structures (IMPIPS) against diseases scourging humankind, malaria being one of them.